Using drama as a teaching tool for second language learning - Nur Haziqah Rosidin (2019)
Language acquisition occurs when language is being used meaningfully. Drama provides ample opportunities to use language meaningfully. The context in drama mimics real-life interactions that allows exploration of different language structures such as tenses, vocabulary and pronunciation. But more importantly, what makes drama a possible platform for language learning is the psychologically safe environment it creates for students to experiment and make mistakes without any consequences. This study is a form of action research that explores the use of drama as a teaching pedagogy for a Malay language structure: simpulan bahasa. Four drama workshops were conducted over four consecutive days at Xingnan Primary School. 21 Primary 3 students were introduced to six simpulan bahasa. Quantitative results showed an increase in mean test scores before and after the drama workshops. Qualitative results gathered participants’ work during the workshop and found that participants were able to apply the meaning of the simpulan bahasa into different contexts. The benefits of drama extended into aiding conceptual blending of abstract meanings and into social and emotional learning. The results from this study help to justify the rationale of using drama as a teaching pedagogy for effective second language learning due to its real meaningful interactions.